Promoting New Ways of Teaching and Learning in Science Education with Student-created Digital Animations : Final Report. - Clark, Julie; Hoban, Garry (Office for Learning and Teaching, 2012)
Science education academics need to incorporate new ways of teaching and learning to engage student teachers in science knowledge. 'Slowmation' (abbreviated from 'Slow-motion Animation') is a new teaching approach that encourages students to use their own technologies and create a narrated digital animation to explain a science concept that is played in slow motion at two frames/second (Hoban, 2005, 2007). It is a form of stop-motion animation that integrates features of clay animation, object animation and digital storytelling and encourages students to design a multimodal representation of their learning. This is the final report from an ALTC project that embedded and upscaled the new teaching approach to science education academics across Australia who instruct either early childhood, primary or secondary science teacher education students. New resources in the form of modules demonstrating animation skills and exemplars of implementation in university classes were designed to support implementation. This was accompanied by development of a professional learning community of science education academics to enhance dissemination.